Unspoken : a story from the Underground Railroad - Cole, Henry, 1955- (New York : Scholastic Press, 2012)
In this wordless picture book, a young Southern farm girl discovers a runaway slave hiding behind the corn crib in the barn and decides to help him.
Keywords: Underground Railroad -- Juvenile fiction; Fugitive slaves -- Juvenile fiction; African Americans -- Juvenile fiction